2016
DOI: 10.4028/www.scientific.net/kem.693.548
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Automaton Modeling of Dynamic Recrystallisation Microstructure Evolution for 316LN Stainless Steel

Abstract: Based on the theoretical model and physical mechanism of dynamic recrystallization (DRX) in metal materials, the dislocation density change, nucleation and grain growth model during the process of DRX are taken into account. And according to the nucleation driven by dislocation and grain growth kinetic, transformation rules are made. A modeling methodology coupling fundamental metallurgical principles based on amended nucleation rate with the cellular automaton (CA) technique is here derived to simulate the 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…They reported an adaptive response surface method as an optimization model to provide input parameters of the CA model. Recently, Li et al [18] and Haipeng et al [19] have investigated the effects of process parameters on the fraction of DRX and the average recrystallization grain size using the CA approach, and showed that the results are in good agreements with the experiments. Generally in CA modeling, initial grain size, initial grain orientation, and dislocation density are used as input data and flow curve, dislocation density, final grain size, and DRX volume fraction are the output data [20,21].…”
Section: Introductionmentioning
confidence: 83%
“…They reported an adaptive response surface method as an optimization model to provide input parameters of the CA model. Recently, Li et al [18] and Haipeng et al [19] have investigated the effects of process parameters on the fraction of DRX and the average recrystallization grain size using the CA approach, and showed that the results are in good agreements with the experiments. Generally in CA modeling, initial grain size, initial grain orientation, and dislocation density are used as input data and flow curve, dislocation density, final grain size, and DRX volume fraction are the output data [20,21].…”
Section: Introductionmentioning
confidence: 83%
“…The boundary condition, also referred to as periodic condition, is the first condition type. It is used, among other things, for the simulation of the recrystallization process of hot deformed austenite of TRIP steel [ 23 ], in the modeling of grain coarsening and refinement during the dynamic recrystallization of pure copper [ 24 ], in two-dimensional CA with the quadrilateral element, or in the modeling of dynamic recrystallization microstructure evolution for 316LN stainless steel [ 25 ]. This type of boundary connects the boundaries of the cellular space and allows introduction of the dependence between their different parts.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…They implemented the input parameters by using an adaptive response surface method. Recently, Haipeng et al [34], Zhang et al [35] and Li et al [36] have studied influences of the hot deformation variables on the microstructural features of recrystallized grains via the CA approach, and proved the high precision of the simulated results. Azarbarmas and Aghaie-Khafri [37] have lately presented a CA model coupled with a rate-dependent model to simulate the DDRX phenomenon during the hot deformation of Inconel 718, and showed the good ability of the CA model in coupling with other models.…”
Section: Introductionmentioning
confidence: 99%